The Effect of Binahong Leaf (Anredera Cordifolia) on Hemoglobin Levels in Anemic Pregnant in the Coastal Area of North Konawe District - S, Wahida; Saraswati, Endah; Nurdjaya, Malahayati; Amdadi, Zulaeha A. (Al Makki Publisher, 2024)
Binahong leaves (Anredera cordifolia) in several regions in Indonesia are known as gandola which is usually used as a hedge plant. Binahong is believed to be an herbal plant that can bring health benefits. All parts of this plant such as roots, stems and leaves can be used in herbal medicine. One of the nutrients contained in binahong leaves is iron, namely in 100 grams there is 0.4 grams of iron. The research aims to determine the effect of giving decoction of Binahong leaves to pregnant women who experience anemia in the Coastal Area of North Konawe Regency. The results of this research are that giving binahong (Anredera cordifolia) decoction shows that there is a difference in the Hb levels of pregnant women between before and after being given binahong leaves (intervention group).